Complementation of intramolecular interactions for structural-functional stability of plant serine proteinase inhibitors - Joshi, Rakesh S.; Mishra, Manasi; Suresh, C. G.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Plant protease inhibitors (PIs) constitute a diverse group of proteins capable of inhibiting proteases. Among Pls, serine Pls (SPIs) display stability and conformational restrictions of the reactive site loop by virtue of their compact size, and by the presence of disulfide bonds, hydrogen bonds, and other weak interactions. Scope of review: The significance of various intramolecular interactions contributing to protein folding mechanism and their role in overall stability and activity of SPIs is discussed here. Furthermore, we have reviewed the effect of variation or manipulation of these interactions on the activity/stability of SPIs. Major conclusions: The selective gain or loss of disulfide bond(s) in SPIs can be associated with their functional differentiation, which is likely to be compensated by non-covalent interactions (hydrogen bonding or electrostatic interactions). Thus, these intramolecular interactions are collectively responsible for the functional activity of SPIs, through the maintenance of scaffold framework, conformational rigidity and shape complementarities of reactive site loop. General significance: Structural insight of these interactions will provide an in-depth understanding of kinetic and thermodynamic parameters involved in the folding and stability mechanisms of SPIs. These features can be explored for engineering canonical SPIs for optimizing their overall stability and functionality for various applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Disulfide bond; hydrogen bonding; Intramolecular weak interaction; Protease; Reactive site loop; Serine proteinase inhibitor

Cyclic peptide engineered from phytocystatin inhibitory hairpin loop as an effective modulator of falcipains and potent antimalarial - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Pandey, Kailash C.; Singh, Shailja (Journal of Biomolecular Structure & Dynamics, 2022)
Cystatins are classical competitive inhibitors of C1 family cysteine proteases (papain family). Phytocystatin superfamily shares high sequence homology and typical tertiary structure with conserved glutamine-valine-glycine (Q-X-V-X-G) loop blocking the active site of C1 proteases. Here, we develop a cysteine-bounded cyclic peptide (CYS-cIHL) and linear peptide (CYS-IHL), using the conserved inhibitory hairpin loop amino acid sequence. Using an in silico approach based on modeling, protein-peptide docking, molecular dynamics simulations and calculation of free energy of binding, we designed and validated inhibitory peptides against falcipain-2 (FP-2) and -3 (FP-3), cysteine proteases from the malarial parasite Plasmodium falciparum. Falcipains are critical hemoglobinases of P. falciparum that are validated targets for the development of antimalarial therapies. CYS-cIHL was able to bind with micromolar affinity to FP-2 and modulate its binding with its substrate, hemoglobin in in vitro and in vivo assays. CYS-cIHL could effectively block parasite growth and displayed antimalarial activity in culture assays with no cytotoxicity towards human cells. These results indicated that cyclization can substantially increase the peptide affinity to the target. Furthermore, this can be applied as an effective strategy for engineering peptide inhibitory potency against proteases.
Keywords: Cyclic peptide; falcipain inhibitors; falciparum; P; Phytocystatin; protein interaction mimics; protein&#8211